UJI EFEKTIVITAS MINYAK ATSIRI SERAI WANGI (Cymbopogon nardus L.) DALAM MENGENDALIKAN JAMUR (Alternaria porri) PENYEBAB PENYAKIT BERCAK UNGU PADA TANAMAN BAWANG PREI (Allium Fistulosum L.) - Abifah, Serlia Nur; Prasetyawati, Endang Triwahyu; Suryaminarsih, Penta (Universitas Lampung, 2025)
The growth and production of oil palm is greatly influenced by the presence of Plant Pest Organisms (OPT), one of which is purple spot disease caused by the fungus Alternia porri. Control efforts using vegetable fungicides, namely citronella essential oil. The aim of this research is to determine the concentration of citronella essential oil as a vegetable fungicide that is effective in suppressing the growth of the Alternaria porri fungus in vitro. This research was carried out from October-December 2023. The location of this research was carried out at the Plant Health Laboratory, Faculty of Agriculture, National Development University